NBA Pre-Draft Combine is the weak predictor of rookie basketball player`s performance - Ranisavljev, I.; Mandic, R.; Cosic, M.; Blagojevic, P.; Dopsaj, M. (Journal of Human Sport & Exercise, 2021)
The goal of the study was to assess the relationship between rookie player`s Pre-Draft Combine physical abilities and basketball performance in the first NBA season. In strictly homogenized sample of players (N = 58) who matched the inclusion criterion of average playing time and number games in the period 2012-2015, the results indicate that Pre-Draft Combine testing procedures show low to moderate correlations with only few observed basketball performance variables in the first NBA season. The highest correlation was found between upper body strength and number of rebounds (r = .403, p = .002) and blocked shots (r = .333, p = .011). Regression model of Combine performance explained 24.7% of basketball performance with three physical performance tests. Practical application might suggest that some parts of the Combine might be restructured in order to include some other tests more informative tests for the future player performance and player selection.